Paradictyoarthrinium chiangmaiense (Paradictyoarthriniaceae, Pleosporales), a novel microfungus from northern Thailand - Chen, Xue-Mei; Karunarathna, Samantha C.; Zhang, Xian; Kumla, Jaturong; Yu, Fuqiang; Alfagham, Alanoud T.; Elgorban, Abdallah M.; Tibpromma, Saowaluck; Suwannarach, Nakarin (Phytotaxa, 2025)
During the investigation of saprobic microfungi in Chiang Mai Province, Thailand, a black fungal mass on dead wood was collected and isolated. Based on initial morphology, this fungus was tentatively identified as a Dictyoarthrinium-like taxon. Phylogenetic analyses of combined ITS, LSU, and rpb2 sequences revealed that it belongs to a new taxon in the genus Paradictyoarthrinium. This novel taxon exhibits morphological characteristics typical of Paradictyoarthrinium, with gregarious, black, powdery colonies featuring macronematous conidiophores and unevenly dictyoseptate, muriform conidia. Based on morphological features similar to those of closely related species, the pairwise homoplasy index (PHI) test was used as an additional method to assess the likelihood of homoplasy within the dataset. The results indicated no significant genetic recombination (Φw = 0.9938) between all closely related species and our collection. Therefore, we propose our collection as a new species, P. chiangmaiense, accompanied by a description, illustrations, and a phylogenetic tree to illustrate its placement within the genus.